Pengaruh Back massage terhadap Kualitas Tidur Ibu Hamil Trimester III di Praktik Mandiri Bidan Dince Syafrina Kota Pekanbaru: The Effect of Back massage on the Quality of Sleep of Third Trimester Pregnant Women in Independent Practice Midwife Dince Syafrina, Pekanbaru City - Yanti, Yanti; Deswita Afriyeni; Susilawati, Elly; Rahmadona, Rahmadona (Poltekes Kemenkes Tanjungpinang, 2024)
Sleep disturbances are one of the discomforts of third-trimester pregnant women that affect the quality of sleep. One of the non-pharmacological methods to help reduce sleep disturbances is back massage. The study aimed to determine the effect of back massage on third-trimester pregnant women's sleep quality. This type of research was pre-experimental, using the One Group Pretest Posttest Design approach. The population in this study was a third-trimester pregnant woman who checked her pregnancy at PMB Dince Safrina Pekanbaru City in February-March 2023. The sample in this study amounted to 15 pregnant women in the third trimester who had a PSQI score > 5, which was taken by purposive sampling. The data collection method was observation using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results showed that the average sleep quality of pregnant women before the intervention was 7.67 (Sd = 1.34), and the average sleep quality after the back massage intervention. 5.73 (Sd = 0.69). Based on statistical tests, back massage affected the sleep quality of pregnant women in the third trimester (pvalue= 0.001). It is expected that health workers, especially midwives at PMB Dince Safrina, can apply back messaging as a non-pharmacological therapy for treating sleep disorders in third-trimester pregnant women.